연구윤리교육 필요성 인식 및 영향요인 - 성정민; 박용덕 (Han'guk Ch'iwisaeng Hakhoe chi, 2012)
Objectives : The purpose of this study was to examine the professors, who teach the dental hygiene program in Korea, on the awareness of the research ethics education check. And attempt to provide and promote a basic foundation for future research ethics education Methods : Questionnaire survey was carried out targeting 119, who teach the dental hygiene program. The collected data was performed frequency & percentage, independent t-test and one-way ANOVA, Pearson's correlation coefficient and multiple regression. Results : 1. As recognition about research ethics education needs, they expressed the biggest recognition that research ethics education is required(3.66±0.57) 2. Regarding the correlation between students needs research ethics education and interested research ethics education had a statistically significant correlation of r=0.381which was the highest correlation factor. 3. Research ethics education taking institutions, 39.4% respondents experienced the biggest national research institutes. 4. Between general characteristics and research ethics education recognition level, they were statistically significantly different with age and major course(p<0.05). 5. The affecting factors on the research ethics education were teaching career and number of articles published as the first author, explained 12.8%(p<0.001). Conclusions : Research ethics education is desperately needed. Therefore I will insist the case based approach in the research ethics education program with the format of a stand course. KCI Citation Count: 8